Barriers to Lean Manufacturing Implementation in the Bakery Industry: An Empirical Study from Indonesia - Caroline Felicita Aurelius; Mangngenre, Saiful; Setiawan, Irwan (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
The implementation of lean manufacturing is essential for companies to minimize waste by reducing non-value-added activities while maintaining product quality and customer satisfaction. Despite its advantages, various barriers hinder its optimal application. This study aims to identify the factors that impede the implementation of lean manufacturing and determine the most dominant factors in bakery factories in Indonesia. The research was conducted across 14 bakery factories on the islands of Sumatra, Java, Kalimantan, and Sulawesi. Data was collected using a survey questionnaire and analyzed using factor analysis and the Decision Making and Evaluation Laboratory (DEMATEL) method. The results reveal seven key factors with significant influence, with technology emerging as the most dominant factor (1.404), followed by organizational culture (0.497). These findings underscore the importance of addressing the technological limitations and organizational culture to enhance lean manufacturing efficiency. The practical implications of this study suggest that bakery companies should focus on improving their technological infrastructure and fostering a culture supportive of lean principles to optimize production efficiency. Theoretical implications include the extension of lean manufacturing frameworks to address sector-specific challenges in the bakery industry, contributing to the broader field of sustainable manufacturing practices